Hyperoxia causes miR-34a-mediated injury via angiopoietin-1 in neonatal lungs. Issue 1 (December 2017) - Syed, Mansoor; Das, Pragnya; Pawar, Aishwarya; Aghai, Zubair; Kaskinen, Anu; Zhuang, Zhen; Ambalavanan, Namasivayam; Pryhuber, Gloria; Andersson, Sture; Bhandari, Vineet
Abstract Hyperoxia-induced acute lung injury (HALI) is a key contributor to the pathogenesis of bronchopulmonary dysplasia (BPD) in neonates, for which no specific preventive or therapeutic agent is available. Here we show that lung micro-RNA (miR)-34a levels are significantly increased in lungs of neonatal mice exposed to hyperoxia. Deletion or inhibition of miR-34a improves the pulmonary phenotype and BPD-associated pulmonary arterial hypertension (PAH) in BPD mouse models, which, conversely, is worsened by miR-34a overexpression. Administration of angiopoietin-1, which is one of the downstream targets of miR34a, is able to ameliorate the BPD pulmonary and PAH phenotypes. Using three independent cohorts of human samples, we show that miR-34a expression is increased in type 2 alveolar epithelial cells in neonates with respiratory distress syndrome and BPD. Our data suggest that pharmacologic miR-34a inhibition may be a therapeutic option to prevent or ameliorate HALI/BPD in neonates. Hyperoxia contributes to lung injury in bronchopulmonary dysplasia. The authors show that hyperoxia increases miR-34a expression in human neonates and in mouse models, and that pathology is ameliorated by miR-34a inhibition or by administration of its target angiopoietin-1